LEGAL ISSUES OF THE HUAULU COMMUNITY: INTERACTION OF THE PEOPLE WITH SOCIAL-LEGAL MAPPING - Syah Awaluddin; Nurlaila Sopamena; Rahmat MZ; Marlon Alaiye; Irvan Ipatapale (Pedagogic Research-Applied Literacy Journal, 2024)
One of the indigenous communities in Maluku that faces a number of legal issues in their daily lives is the Huaulu community. This study employs a socio-legal method to identify important legal concerns and advocacy tactics that can assist the Huaulu people in more fairly and equally obtaining their rights. According to the mapping results, the Huaulu community still faces social stigma, restricted educational opportunities, civil administration obstacles, and inequalities in legal protection, all of which have a substantial influence on their rights as citizens. A community service program was put in place as a remedy to deal with these problems. The purpose of this article is to identify the legal issues that the Huaulu community faces and provide community-based remedies through activism, legal education, and administrative support. The report aims to support Indonesia's acknowledgment and defense of indigenous rights by combining policy recommendations with legal empowerment.